(2013) Minister Wert's first year of educational policy - Sanjosé, Jesús (Razón y fe, 2018)
In the previous article 1, the need to interpret the actions that the minister of education is carrying out based on whether or not they meet the objectives set out in the program - with which the PP won the last elections - was raised. To this end, a distinction was made between actions in the short, medium and long term, and the development of the LOMCE was placed among the latter, recalling that the PP, although they are, for a second time, in a position to develop a rule of this scope, it would be the first that (once finished) could enter into force. The objective of this article is to present in detail, in a critical way, the new norm that, under the acronym of LOMCE, is currently in the Congress of Deputies and that, after its approval, will govern non-university Spanish education of the next few years.